KONTRIBUSI MINAT BELAJAR TERHADAP HASIL BELAJAR KONSTRUKSI BANGUNAN GEDUNG KELAS XI JURUSAN TEKNIK KONSTRUKSI BANGUNAN SMKN 2 BANDA ACEH - Lia Adriana; Drs. Juniman Silalahi, M.Pd (CIVED, 2019)
Abstract—. The research was conducted in smkn 2 banda aceh and based on the following conditions there are still many grader student of majoring in the construction of buildings smkn 2 banda aceh that they received a score under kkm on the subjects of the construction of buildings the building.The contribution of this study aims to to express preference for school learning of the results of the building construction grader student of majoring in the construction of buildings smkn 2 banda aceh.The kind of research used is research with the approach of correlational quantitative. descriptiveThe population is majoring in grader student of building as many as 36 people.Using a technique the total sample the sampling method of. The primary data was collected through such research to be distributed to respondents.Secondary data research obtained from subject teachers the construction of buildings buildings in the forms of uas value grader student of majoring in the construction of buildings.The technique of analysis of the data used was: ( 1 ) descriptive analysis, ( 2 ) test the requirements of the analyses consisting of the trial normality and test it linieritas ( 3 ) an hypothesis. testIt can be concluded from the research there is the contribution of the results of preference for school learning the construction of buildings buildings in smkn 2 banda aceh as much as 76,03 %.Keywords: interest, learning outcomes